Highly sensitive and selective sensing of ascorbic acid in water with a three-dimensional terbium(III)-based coordination polymer. (5th November 2021) - Zhao, Xiao-Yang; Wang, Jia; Yang, Qi-Shan
Graphical abstract: Highlights: A 3D terbium(III)-based coordination polymer by dual-ligands is synthesized. The supramolecular architecture is constructed by hydrogen bonding interactions. Energy transfer process between the two ligands and Tb 3+ is clearly explained by DFT. The characteristic fluorescence of Tb 3+ be significantly quenched by ascorbic acid. The detection mechanism is discussed in detail based on the frontier orbital theory. Abstract: Ascorbic acid (AA), an essential nutrient in the human body, is an antioxidant that protects the body from the threat of free radicals. The sensitive, efficient and rapid detection of AA has far-reaching significance in human health, biomedicine and food-related science. Herein, pyromellitic acid (H4 btec) and nicotinic acid (Hntca) were used as ligands to synthesize a novel terbium-based coordination polymer ([Tb(Hbtec)(Hntca)(H2 O)3 ]·H2 O) under solvothermal conditions, which was interlaced by coordination bonds and hydrogen bonds to form an infinitely extended three-dimensional supramolecular structure. The two ligands as "antenna molecules" could effectively sensitize Tb 3+ luminescence. The research results showed that AA was selectively recognized by the complex through significant fluorescence quenching response, and it had excellent detection sensitivity (the detection limit is 0.8 μM) and anti-interference ability. The sensor system was successfully applied to the detection of AA in practical samples, so it was expected to be sensitive and efficient AA sensor. In addition, the sensing mechanism was analyzed in detail by the combination of characterization method and density functional theory (DFT), which was attributed to the absorption competition of excitation light energy and the photoinduced electron transfer (PET) process.